Comparison of self-efficacy in cardiopulmonary resuscitation position by a single rescue: over-the-head or lateral position? - Wirmando, Wirmando; Sambo, Mery; Madu, Yunita Gabriela; Beda, Nikodemus Sili; Satti, Yunita Carolina; Sheryn, Sheryn; Batara, Tiara Ayu; Bunga, Lindri (Intelektual Pustaka Media Utama, 2024)
Self-efficacy can speed up and improve quality of cardiopulmonary resuscitation (CPR), but it will be difficult to achieve if using a bag-valve-mask (BVM) by a single rescue. This study aimed to compare the differences of self-efficacy when performing CPR in the lateral and over-the-head (OTH) positions using a BVM device in a single rescue. A quasi-experimental with a post-test-only group design approach. This study involved 100 respondents divided into two groups, namely 50 respondents in the lateral position and 50 in the OTH position. Respondents' self-efficacy was assessed using the resuscitation self-efficacy scale (RSES). The statistical test used was Mann-Whitney. The results of this study showed that the OTH group had a higher level of self-efficacy, 46 (92%), than the lateral group, 40 (80%). In addition, the results of the Mann-Whitney statistical test also obtained p-value=0.000 (α=0.05) and mean rank value (OTH=63.30, lateral=37.70), indicating that there was a difference in self-efficacy between the OTH and lateral positions, with the OTH group having higher self-efficacy compared to the lateral group. Therefore, if CPR is performed by a single rescue with a BVM device, it can be performed with the OTH position.